EFFECT OF THERMOSONICATION ON FERRIC REDUCING ANTIOXIDANT POWER AND THE COLOR OF BERAS KENCUR DRINK - Serly Safitri; Sri Winarti; Luqman Agung Wicaksono; Anugerah Dany Priyanto; Wildan Naufal Esfandiar; Almira Dinar Dhiny (Jurnal Pangan dan Agroindustri, 2022)
Beras kencur drink is an Indonesia’s traditional beverage containing several antioxidant compounds that are good for human health. Thermosonication technology was chosen to process the beras kencur drink. This research aimed to evaluate antioxidant activity and the color of beras kencur drink thermosonication with compared to the control untreated and pasteurization treatment. The thermosonication treatment used a probe at a frequency of 22 kHz, while conventional pasteurization conditions were 100oC for 2 min. This study employed a Completely randomised design (CRD) with two factorials; temperatures of thermosonication (30, 45 and 60 oC) and times of thermosonication (5, 10, 15 min). The data were analyzed by ANOVA followed by DMRT with p-value greater than 0.05. The results showed that the effects of thermosonication on antioxidant activities and the color of beras kencur drink were more retention than the pasteurization treatment. The value antioxidant activity of beras kencur drink treated with thermosonication ranged from 1164.80 – 1323.86 mgAA/L, and the color values ranged from 58.16 – 62.58 for lightness (L*), 0.42 – 1.30 for redness (a*), 20.70 – 22.53 for yellowness (b*) and 0.50 – 5.29 for total color difference.